Badania elektrofizjologiczne we wczesnej diagnostyce i różnicowaniu niektórych uwarunkowanych genetycznie chorób siatkówki i nerwu wzrokowego - Lubiński, Wojciech; Palacz, Olgierd; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: The goal of our study was to determine the value of electrophysiological tests in early and differential diagnosis of some hereditary retinal and optic nerve diseases. Material and methods: Review article on the basis of own experiences and results of another authors concerning to EOG, ERG, PERG, MfERG and VEP tests in evaluation of hereditary, stationary and progressive retinal diseases, as well as optic nerve diseases. Results: Electrophysiological tests can be abnormal even in patients without fundus changes seen in routine ophthalmological examination. Conclusions: Electrophysiological tests are useful in early and differential diagnosis of some hereditary retinal and optic nerve diseases. General ophthalmologists should remember about its application, especially in difficult diagnostic cases.